(untitled) (Acta Scientiarum. Biological Sciences, 2011)
The essential oil from the fresh leaves of Lippia microphylla Cham. was obtained by hydrodistillation and characterized by gas chromatography-mass spectrometry (GC-MS). Major constituents of the oil were 1.8-cineole (18.12%), β-ocimene (15.20%), bicyclogermacrene (11.63%) and caryophyllene oxide (8.32%). Antimicrobial activity of the oil against Gram-positive and Gram-negative bacteria was determined by gel diffusion method. The oil showed good antibacterial activity against Shigella flexneri, Escherichia coli and Streptococcus pyogenes and very good antibacterial activity against Staphylococcus aureus.